APLIKASI PERPUSTAKAAN BERBASIS DESKTOP: STUDI KASUS PKBM BINA MANDIRI - Meriyani; M. Syafiuddin Usman (Jurnal Penelitian Multidisiplin Ilmu, 2023)
Desktop-based applications seem to have become a necessity for organizations, agencies, companies and so on. The need is usually not only for promotion, but also business activities. The purpose of this desktop-based library application is to facilitate the borrower in the borrowing process, facilitate the process of returning books and find what books we want at Bina Mandiri PKBM Agency.Due to the Bina Mandiri PKBM Agency does not yet have a desktop-based library application, therefore the author makes a desktop as an alternative to updated information media by providing online-based book lending services. In this application, the author uses the PHP programming language, XAMPP with Visual Studio Code as a text editor, while the data base used is MySQL.Desktop-based applications are considered effective as an alternative media to provide information and book lending services to students, besides that with the existence of desktop-based applications and online book lending, it is hoped that with the creation of this application libraries in this day and age have more value than a library system that is processed manually or handwritten and will also produce an efficient system and have high productivity.